2017
DOI: 10.1016/j.concog.2017.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Ageing and thought suppression performance: Its relationship with working memory capacity, habitual thought suppression and mindfulness

Abstract: A study investigated how the ability to suppress thoughts in the laboratory was affected by type of thought suppressed (positive, negative, neutral), participants' age and working memory capacity (WMC). Linked variables (Use of thought suppression, social desirability, and mindfulness) were measured to assess whether they modified susceptibility to thought intrusion. Younger, middle aged and older adults suppressed three different valenced thoughts in a counterbalanced order for 5-min per thought. Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…Working memory does have finite attentional resources available. In line with the perceptual load theory of attention (Lavie & Tsal, 1994 ), a high perceptual load of attention on other material (in our study: the breath) may prevent unwanted distractors from intruding (Erskine et al, 2017 ). This principle may explain the observed phenomenon that focusing on the breath diminished the mental space available for distressing thoughts.…”
Section: Discussionsupporting
confidence: 82%
“…Working memory does have finite attentional resources available. In line with the perceptual load theory of attention (Lavie & Tsal, 1994 ), a high perceptual load of attention on other material (in our study: the breath) may prevent unwanted distractors from intruding (Erskine et al, 2017 ). This principle may explain the observed phenomenon that focusing on the breath diminished the mental space available for distressing thoughts.…”
Section: Discussionsupporting
confidence: 82%
“…Generally, this method is referred to as event marking, to distinguish it from other forms of thought assessment that do not require participants to actively report the occurrence of a target thought, such as thought sampling (e.g., Hirsch, Perman, Hayes, Eagleson, & Mathews, 2015) or the think-aloud technique (Erskine, Georgiou, Joshi, Deans, & Colegate, 2017;Lavy & Vandenhout, 1990). During thought sampling, participants may think about whatever they want during a predefined period and are asked at several time points (e.g., 12 times in a 6-min period) to briefly indicate their thought content (i.e., whether they are currently thinking of the target thought).…”
Section: Introductionmentioning
confidence: 99%
“…All our actions consist in thoughts. Erskine et al [10] have studied about type of thoughts which may suppress candidate"s age and working memory capacity and concluded that the aging may reduce intrusive thoughts. Good habits are extremely valuable for everyone.…”
Section: Introductionmentioning
confidence: 99%